2020
DOI: 10.1126/sciadv.abb9414
|View full text |Cite
|
Sign up to set email alerts
|

Parabrachial neuron types categorically encode thermoregulation variables during heat defense

Abstract: Heat defense is crucial for survival and fitness. Transmission of thermosensory signals into hypothalamic thermoregulation centers represents a key layer of regulation in heat defense. Yet, how these signals are transmitted into the hypothalamus remains poorly understood. Here, we reveal that lateral parabrachial nucleus (LPB) glutamatergic prodynorphin and cholecystokinin neuron populations are progressively recruited to defend elevated body temperature. These two nonoverlapping neuron types form circuits wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 64 publications
4
66
0
1
Order By: Relevance
“…These FISH based experiments indicate that Pdyn + and Penk + cells in the LPBN express Slc17a6 and are partially overlapping subpopulations of glutamatergic LPBN cells. A recent report on PBN→POA neurons implicated cholecystokinin (Cck) expressing LPBN neurons in heat defense ( Yang et al, 2020 ). We examined if Pdyn labeled neurons in LPBN were co-labeled by probes for Cck and found that 70% ± 0.7 (mean ± SEM, n = 150 cells, n = 3 mice) of LBP Pdyn labeled neurons were co-labeled by Cck probes (Supplemental Figure 2—figure supplement 2D–F ) suggesting that mRNA for Cck and pDyn is expressed in overlapping neuronal populations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These FISH based experiments indicate that Pdyn + and Penk + cells in the LPBN express Slc17a6 and are partially overlapping subpopulations of glutamatergic LPBN cells. A recent report on PBN→POA neurons implicated cholecystokinin (Cck) expressing LPBN neurons in heat defense ( Yang et al, 2020 ). We examined if Pdyn labeled neurons in LPBN were co-labeled by probes for Cck and found that 70% ± 0.7 (mean ± SEM, n = 150 cells, n = 3 mice) of LBP Pdyn labeled neurons were co-labeled by Cck probes (Supplemental Figure 2—figure supplement 2D–F ) suggesting that mRNA for Cck and pDyn is expressed in overlapping neuronal populations.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together these results indicated that Pdyn+ and Penk+ PBN→POA neurons represent subsets of the glutamatergic warm-activated PBN neurons. A recent report presented data indicating the Pdyn vs Cck expression in the PBN marked a functional division of neurons driving vasodilation and BAT regulation ( Yang et al, 2020 ). In contrast to those results, we found that Pdyn and Cck expression overlap in many lateral PBN neurons and that activation of Pdyn+ PBN→POA neurons induces tail vasodilation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CC-BY 4.0 International license made available under a (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. It is The copyright holder for this preprint this version posted April 11, 2021. ; https://doi.org/10.1101/2021.04.11.439314 doi: bioRxiv preprint control signals and vasodilation control signals (Yang et al 2020). Signals are integrated in the preoptic area (POA) and then POA neurons directly target neurons in the DMH or the raphe pallidus nucleus (RPa) to drive different aspects of thermal effector activities, such as brown adipose tissue (BAT) thermogenesis and vasodilation (Tan & Knight 2018;Morrison & Nakamura 2019).…”
Section: Introductionmentioning
confidence: 99%